1990
DOI: 10.1111/j.1365-2672.1990.tb02913.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychrotrophic strains of Bacillus cereus producing enterotoxin

Abstract: In investigations on three outbreaks of Bacillus cereus food poisoning in Spain and The Netherlands, the causative strains grew within a temperature range of 4-37 degrees C, but not at 43 degrees C. Such psychrotrophic types were found to occur in various dairy products (including ca 25% of 35 samples of pasteurized milk) and some mousses and cook/chill meals. Growth of and enterotoxin production by psychrotrophic B. cereus could be prevented by temperatures below 4 degrees C and pH-values not exceeding 5.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…In a first systematic approach we compared enterotoxin gene expression of a representative B. cereus strain set. Previous studies compared enterotoxin expression in single B. cereus strains under varying growth temperature (Van Netten et al, 1990 ; Fermanian et al, 1997 ; Rejasse et al, 2012 ), oxygen availability (Duport et al, 2004 ; Van Der Voort and Abee, 2009 ), lowered oxidation-reduction potential (ORP) (Duport et al, 2006 ; Zigha et al, 2007 ; Esbelin et al, 2009 ) and differing availability of nutrients, for instance sugars (Ouhib et al, 2006 ; Ouhib-Jacobs et al, 2009 ). In our study, quantification of nheB and hblD mRNA levels at early exponential and late exponential growth phase/transition phase by qRT-PCR revealed highly strain-dependent variations in toxin gene transcript levels and transcription efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In a first systematic approach we compared enterotoxin gene expression of a representative B. cereus strain set. Previous studies compared enterotoxin expression in single B. cereus strains under varying growth temperature (Van Netten et al, 1990 ; Fermanian et al, 1997 ; Rejasse et al, 2012 ), oxygen availability (Duport et al, 2004 ; Van Der Voort and Abee, 2009 ), lowered oxidation-reduction potential (ORP) (Duport et al, 2006 ; Zigha et al, 2007 ; Esbelin et al, 2009 ) and differing availability of nutrients, for instance sugars (Ouhib et al, 2006 ; Ouhib-Jacobs et al, 2009 ). In our study, quantification of nheB and hblD mRNA levels at early exponential and late exponential growth phase/transition phase by qRT-PCR revealed highly strain-dependent variations in toxin gene transcript levels and transcription efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…B. cereus is ubiquitous in soil, rive, spices, milk, and vegetables and on human skin [4]. In a previous study on the microbiological quality of fresh vegetables, the most frequent foodborne prevalence and characteristics of psychrotolerant B. cereus strains from foodstuff such as milk, dairy products, and chilled food [17,18,24]. Therefore, the goal of the present study was to evaluate the presence and toxigenic characteristics of B. cereus strains, especially psychrotolerant B. cereus strains in green leaf lettuce as an example of leafy vegetables distributed in cold chain.…”
Section: Introductionmentioning
confidence: 99%
“…A reverse passive latex bead agglutination (RPLA) test kit produced by Oxoid was employed in this work to detect B. cereus diarrhoeagenic toxin. The kit has been previously used by others (Van Netten et al 1990;Griffiths, 1990). Van Netten et al (1990, while showing that strains producing diarrhoea in food poisoning outbreaks were also found positive in the RPLA test, commented that the specificity of the RPLA kit was not confirmed by other means.…”
Section: Discussionmentioning
confidence: 99%
“…A psychrotrophic strain of B. cereus (HRM 44), which is held in the Hannah Research Institute culture collection and which was previously found by Griffiths (1990) to be toxigenic, was used throughout. Diarrhoeagenic toxin was detected using a latex bead immunoassay from Oxoid Ltd (Basingstoke RG24 OPW; Griffiths, 1990;Van Netten et al 1990). Results were reported as a reciprocal titre, which is the reciprocal of the highest dilution of sample giving a positive result in the assay.…”
Section: Bacterial Strain and Toxin Assaymentioning
confidence: 99%